A case of non-islet cell tumor hypoglycemia associated with pancreatic neuroendocrine tumor - Ylli, Agron; Husi, Gerond; Sanxhaku, Renta; Doracaj, Ditila; Vyshka, Gentian; Cakoni, Ruden; Çakërri, Luljeta (Journal of Emergency and Critical Care Medicine; Vol 2 (September 2018): Journal of Emergency and Critical Care Medicine, 2018)
Hypoglycemia of unexplained origin might in rare cases be related with a non-islet cell pancreatic tumor. We report a case of non-islet cell tumor hypoglycemia (NICTH) due to a moderately differentiated neuroendocrine pancreatic carcinoma. A 45-year-old female was admitted to the Service of Endocrinology, following recurrent episodes of severe hypoglycemia. Detected glucose blood values during such episodes were as low as 22 mg/dL. Laboratory and diagnostic imaging tests were performed. The abdominal MRI scan with intravenous contrast was performed and it detected a structure in the tail of the pancreas with dimensions 20 mm × 15 mm. The findings of the MRI indicated a neuroendocrine tumor (NET) of the pancreas tail. Histological post-surgery examination concluded in favor of a moderately differentiated neuroendocrine carcinoma of the pancreas (NECG2). No values of low blood glucose levels were detected after the surgical resection of the tumor. Clinicians should take into account the possibility of NICTH when laboratory and immunohistochemical data do not support more common diagnostic occurrences, such as of insulinoma.